2017
DOI: 10.1093/jncimonographs/lgx008
|View full text |Cite
|
Sign up to set email alerts
|

Including the Patient Voice in Patient-Centered Outcomes Research in Integrative Oncology

Abstract: The objective of this paper is to describe our experience as patient advisors as we work on a Patient-Centered Outcomes Research Institute-funded project, CHoosing Options for Insomnia in Cancer Effectively (CHOICE). The CHOICE Study is a comparative effectiveness trial comparing acupuncture with cognitive behavioral therapy for insomnia in cancer survivors. We describe the composition of the patient advisory panel, the patient engagement process, and our contributions throughout the study, and we highlight so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…How to integrate acupuncture into pain and symptom management plans for patients with cancer remains a challenge. With the move to patient-centered care and personalized medicine in cancer therapy, oncological practice and palliative care services need to provide information about treatment options and ways to access them, which can include evidence-based nonpharmacological approaches . Given that pain is a common reason that patients with cancer visit emergency departments, often followed by hospital admission, hospitals need to establish appropriate acupuncture services.…”
Section: Discussionmentioning
confidence: 99%
“…How to integrate acupuncture into pain and symptom management plans for patients with cancer remains a challenge. With the move to patient-centered care and personalized medicine in cancer therapy, oncological practice and palliative care services need to provide information about treatment options and ways to access them, which can include evidence-based nonpharmacological approaches . Given that pain is a common reason that patients with cancer visit emergency departments, often followed by hospital admission, hospitals need to establish appropriate acupuncture services.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, appropriate retrospective and prospective cohort studies incorporating validated patient‐reported outcomes and relevant clinical outcomes can inform how these treatments impact populations in real‐world settings and potentially generate more specific testable hypotheses that can then be confirmed in clinical trials 216 . Consistent with patient‐centered outcomes research, engaging patients and relevant clinical and policy stakeholders in defining research questions and facilitating dissemination efforts are key to generating evidence that actually matters to patients in their specific cultural and societal settings 217,218 …”
Section: Challenges and Opportunities In Researchmentioning
confidence: 99%
“…This dualcenter, parallel group, randomized, comparative effectiveness trial was conducted at the University of Pennsylvania's Abramson Cancer Center in Philadelphia, PA, and at the Memorial Sloan Kettering Cancer Center in New York, NY (ClinicalTrials.gov Identifier: NCT02356575, https://clinicaltrials.gov/ct2/show/NCT02356575). Patient partners, not enrolled in the study, were involved in formulating the research question, selecting interventions and outcomes, recruitment (particularly minority outreach), and data interpretation (14). The pragmatic trial design sought to directly inform patient and clinician decision-making in the real world (15).…”
Section: Pragmatic Trial Designmentioning
confidence: 99%